Laser anti-counterfeiting coating and preparation method thereof, laser transfer film
By optimizing the formula of laser anti-counterfeiting coatings, introducing copolymerization of epoxy ester and acrylate, and adding wear-resistant fillers, the problem of insufficient wear resistance and scratch resistance of the coating is solved, and higher wear resistance and scratch resistance are achieved, ensuring the stability and durability of the anti-counterfeiting function.
Patent Information
- Application Number
- CN202411031760.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-07-29
AI Technical Summary
Existing laser anti-counterfeiting coatings are prone to damage during transportation and use, resulting in failure of anti-counterfeiting functions and inability to effectively protect high-value products and important documents.
By optimizing the formulation composition, epoxy ester containing benzene ring structure and carbon-carbon double bonds are introduced to copolymerize with a variety of acrylates to form a dense mesh structure, increase the microscopic roughness of the surface of the coating, and add wear-resistant fillers to form a polyaniline nanometal rod through the synergistic action of aluminum and nickel, increasing the crosslinking site, thereby improving the hardness and wear resistance of the coating.
It significantly improves the wear resistance and scratch resistance of laser anti-counterfeiting coatings, making the coating more durable and durable, ensuring the stability and durability of anti-counterfeiting functions.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser anti-counterfeiting coatings, and specifically relates to a laser anti-counterfeiting coating and a preparation method thereof, and a laser transfer film. Background Art
[0002] Laser anti-counterfeiting coatings are widely used in the anti-counterfeiting protection of various products, especially in packaging, labels, bills and other fields. Its main function is to prevent the spread and circulation of counterfeit and shoddy products, thereby maintaining market order and consumer rights. In many high-value products and important documents, the wear resistance and scratch resistance of anti-counterfeiting marks are particularly critical. This is because if the anti-counterfeiting coating does not have good wear resistance and scratch resistance, the anti-counterfeiting mark can easily be damaged during transportation and use, which will lead to the failure of the anti-counterfeiting function, making the product or document lose security, which may cause damage to the brand image and consumer interests. Therefore, laser anti-counterfeiting coatings must have excellent wear resistance and scratch resistance to ensure the stability and durability of its anti-counterfeiting function, so as to effectively protect the brand image and safeguard consumer interests. Summary of the invention
[0003] The purpose of the present invention is to provide a laser anti-counterfeiting coating and a preparation method thereof, and a laser transfer film, which are used to improve the wear resistance and scratch resistance of the coating after the laser anti-counterfeiting coating is formed.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a laser anti-counterfeiting coating, the method comprising the following steps:
[0006] S1, take α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl) propane, and ethylene glycol butyl ether, mix them, stir and heat them to 100-110°C, add N,N-dimethylethylamine, stir for 4-6h, and obtain material A;
[0007] S2, take acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, and material A, mix them, reflux and stir at 120-130° C. for 0.5-1h, cool to 75-85° C., add N,N-dimethylethylamine, stir for 20-30min, and obtain material B;
[0008] S3, taking the material B, defoaming agent, wetting agent, adhesion promoter, wear-resistant filler, and deionized water, mixing them, and stirring for 20-30 minutes to obtain the laser anti-counterfeiting coating.
[0009] As a preferred technical solution of the present invention, in step S1, the mass ratio of α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl)propane, ethylene glycol butyl ether, and N,N-dimethylethylamine is 3-4:6-8:10-15:0.01-0.012.
[0010] As a preferred technical solution of the present invention, in step S2, the mass ratio of acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, material A, and N,N-dimethylethylamine is 8-10:20-22:36-38:8-10:0.4-0.6:2-3:10-12:1-2.
[0011] As a preferred technical solution of the present invention, in step S3, the mass ratio of material B, defoamer, wetting agent, adhesion promoter, wear-resistant filler and deionized water is 60-70: 0.6-0.8: 0.6-0.8: 0.6-0.8: 2-3: 12-16.
[0012] As a preferred technical solution of the present invention, the preparation of the wear-resistant filler comprises the following steps:
[0013] S31, mix sodium montmorillonite and deionized water, stir at 70-80°C for 1-2h, add anhydrous ethanol and KH 550, continue stirring for 3-4h, transfer to a ball mill for ball milling, take out, wash, and vacuum dry at 80°C for 7-8h to obtain material C;
[0014] S32, take the material C and deionized water, mix them, stir at 80°C for 30-40min, add aniline and 5-sulfosalicylic acid, continue stirring for 6-7h, cool to room temperature, add ammonium persulfate, aluminum nitrate nonahydrate, and nickel nitrate hexahydrate, stir for 4-5h, add sodium hydroxide solution, stir for 3-4h, let stand for 12-16h, filter, wash the solid phase, and vacuum dry at 40°C for 24h to obtain the wear-resistant filler.
[0015] As a preferred technical solution of the present invention, in step S31, the dosage ratio of the sodium montmorillonite, deionized water, anhydrous ethanol, and KH 550 is 15-20 g: 500 mL: 200-300 mL: 2-3 mL.
[0016] As a preferred technical solution of the present invention, in step S32, the dosage ratio of material C, deionized water, aniline, 5-sulfosalicylic acid, ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, and sodium hydroxide solution is 1-2g: 200mL: 10-11g: 15-16g: 25-26g: 0.2-0.3g: 0.06-0.08g: 20-30mL.
[0017] As a preferred technical solution of the present invention, in step S31, the rotation speed of the ball mill is 400-450r / min; and the time of the ball mill is 30-40min.
[0018] As a preferred technical solution of the present invention, the concentration of the sodium hydroxide solution is 0.1 mol / L.
[0019] As a preferred technical solution of the present invention, the sources of the above-mentioned part of raw materials are as follows:
[0020] α-Eleuropein was purchased from Yichang Zhongyitai Trading Co., Ltd., 2,2-bis-(4-glycolylaminobenzene) propane was purchased from Hubei Nordina Biotechnology Co., Ltd., N,N-dimethylethylamine was purchased from Shanghai McLean Biochemical Technology Co., Ltd., acrylic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., n-butyl methacrylate was purchased from Jiangsu Aowei New Material Technology Co., Ltd., methyl methacrylate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., hydroxypropyl acrylate was purchased from Shandong Xinheng Chemical Co., Ltd., tert-butyl peroxybenzoate was purchased from Taizhou Suze Chemical Materials Co., Ltd., 2,4-diphenyl-4-methyl-1-pentene was purchased from Wuxi Xinhenghui Materials Co., Ltd., defoamer (polyether defoamer, purchased from Wuhan Kamik Technology Co., Ltd.), wetting agent (wetting agent LCN407, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.), adhesion promoter (AKN-6000 adhesion promoter, purchased from Foshan Qianyou Chemical Co., Ltd.), sodium montmorillonite was purchased from Shanghai Jiader Chemical Technology Co., Ltd., KH 550 was purchased from Wuhan Chenxi New Materials Co., Ltd., aniline was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and 5-sulfosalicylic acid was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0021] The laser anti-counterfeiting coating is prepared by the above-mentioned preparation method.
[0022] A laser transfer film comprises the above-mentioned laser anti-counterfeiting coating.
[0023] Beneficial effects of the present invention:
[0024] The laser anti-counterfeiting coating and its preparation method, as well as the laser transfer film disclosed in the present invention optimize the formula composition, introduce epoxy ester containing a benzene ring structure and a carbon-carbon double bond and copolymerize with a variety of acrylates, so as to obtain a denser network structure, increase the surface micro-roughness of the coating, and improve the wear resistance and scratch resistance of the coating; at the same time, wear-resistant fillers are added, and polyaniline nano-metal rods are generated through the synergistic effect of aluminum and nickel to increase the cross-linking sites, so that the coating has a higher hardness, and the wear resistance and scratch resistance of the coating are further improved. DETAILED DESCRIPTION
[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0026] Example 1
[0027] A method for preparing a laser anti-counterfeiting coating comprises the following steps:
[0028] S1, taking α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl)propane, and ethylene glycol butyl ether, mixing, stirring and heating to 100°C, adding N,N-dimethylethylamine, stirring for 4 hours, and obtaining material A; the mass ratio of α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl)propane, ethylene glycol butyl ether, and N,N-dimethylethylamine is 3:6:10:0.01;
[0029] S2. Take acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, and material A, mix them, reflux and stir at 120°C for 0.5h, cool to 75°C, add N,N-dimethylethylamine, and stir for 20min to obtain material B; the mass ratio of acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, material A, and N,N-dimethylethylamine is 8:20:36:8:0.4:2:10:1;
[0030] S3. Mix the material B, polyether defoamer, wetting agent LCN407, AKN-6000 adhesion promoter, wear-resistant filler and deionized water, and stir for 20 minutes to obtain the laser anti-counterfeiting coating; the mass ratio of the material B, polyether defoamer, wetting agent LCN407, AKN-6000 adhesion promoter, wear-resistant filler and deionized water is 60:0.6:0.6:0.6:2:12.
[0031] The preparation of the wear-resistant filler comprises the following steps:
[0032] S31, mix sodium montmorillonite and deionized water, stir at 70°C for 1h, add anhydrous ethanol and KH 550, continue stirring for 3h, transfer to a ball mill for ball milling, take out, wash, and vacuum dry at 80°C for 7h to obtain material C; the amount ratio of sodium montmorillonite, deionized water, anhydrous ethanol, and KH 550 is 15g:500mL:200mL:2mL; the rotation speed of the ball mill is 400r / min; the ball milling time is 30min;
[0033] S32, take the material C and deionized water, mix them, stir at 80°C for 30min, add aniline and 5-sulfosalicylic acid, continue stirring for 6h, cool to room temperature, add ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, stir for 4h, add sodium hydroxide solution, stir for 3h, let stand for 12h, filter, wash the solid phase, and vacuum dry at 40°C for 24h to obtain the wear-resistant filler; the dosage ratio of the material C, deionized water, aniline, 5-sulfosalicylic acid, ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, and sodium hydroxide solution is 1g:200mL:10g:15g:25g:0.2g:0.06g:20mL; the concentration of the sodium hydroxide solution is 0.1mol / L.
[0034] Example 2
[0035] A method for preparing a laser anti-counterfeiting coating comprises the following steps:
[0036] S1. Mix α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl)propane and ethylene glycol butyl ether, stir and heat to 105°C, add N,N-dimethylethylamine, and stir for 4-6 hours to obtain material A; the mass ratio of α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl)propane, ethylene glycol butyl ether and N,N-dimethylethylamine is 3.5:7:13:0.011;
[0037] S2. Take acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, and material A, mix them, reflux and stir at 125°C for 0.8h, cool to 80°C, add N,N-dimethylethylamine, and stir for 25min to obtain material B; the mass ratio of acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, material A, and N,N-dimethylethylamine is 9:21:37:9:0.5:2.5:11:1.5;
[0038] S3. Mix the material B, polyether defoamer, wetting agent LCN407, AKN-6000 adhesion promoter, wear-resistant filler and deionized water, and stir for 25 minutes to obtain the laser anti-counterfeiting coating; the mass ratio of the material B, polyether defoamer, wetting agent LCN407, AKN-6000 adhesion promoter, wear-resistant filler and deionized water is 65:0.7:0.7:0.7:2.5:14.
[0039] The preparation of the wear-resistant filler comprises the following steps:
[0040] S31, taking sodium montmorillonite and deionized water, mixing, stirring at 75°C for 1.5h, adding anhydrous ethanol and KH 550, continuing stirring for 3.5h, transferring to a ball mill for ball milling, taking out, washing, and vacuum drying at 80°C for 7.5h to obtain material C; the amount ratio of the sodium montmorillonite, deionized water, anhydrous ethanol, and KH 550 is 18g:500mL:250mL:2.5mL; the rotation speed of the ball mill is 425r / min; the ball milling time is 35min;
[0041] S32, take the material C and deionized water, mix them, stir at 80°C for 35min, add aniline and 5-sulfosalicylic acid, continue stirring for 6.5h, cool to room temperature, add ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, stir for 4.5h, add sodium hydroxide solution, stir for 3.5h, let stand for 14h, filter, wash the solid phase, and vacuum dry at 40°C for 24h to obtain the wear-resistant filler; the dosage ratio of the material C, deionized water, aniline, 5-sulfosalicylic acid, ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, and sodium hydroxide solution is 1.5g:200mL:10.5g:15.5g:25.5g:0.25g:0.07g:25mL; the concentration of the sodium hydroxide solution is 0.1mol / L.
[0042] Example 3
[0043] A method for preparing a laser anti-counterfeiting coating comprises the following steps:
[0044] S1, take α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl)propane, ethylene glycol butyl ether, mix, stir and heat to 110°C, add N,N-dimethylethylamine, stir for 6 hours, and obtain material A; the mass ratio of α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl)propane, ethylene glycol butyl ether, N,N-dimethylethylamine is 4:8:15:0.012;
[0045] S2. Take acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, and material A, mix them, reflux and stir at 130°C for 1h, cool to 85°C, add N,N-dimethylethylamine, and stir for 30min to obtain material B; the mass ratio of acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, material A, and N,N-dimethylethylamine is 10:22:38:10:0.6:3:12:2;
[0046] S3. Mix the material B, polyether defoamer, wetting agent LCN407, AKN-6000 adhesion promoter, wear-resistant filler and deionized water, and stir for 30 minutes to obtain the laser anti-counterfeiting coating; the mass ratio of the material B, polyether defoamer, wetting agent LCN407, AKN-6000 adhesion promoter, wear-resistant filler and deionized water is 70:0.8:0.8:0.8:3:16.
[0047] The preparation of the wear-resistant filler comprises the following steps:
[0048] S31, mixing sodium montmorillonite and deionized water, stirring at 80°C for 2h, adding anhydrous ethanol and KH 550, continuing stirring for 4h, transferring to a ball mill for ball milling, taking out, washing, and vacuum drying at 80°C for 8h to obtain material C; the amount ratio of the sodium montmorillonite, deionized water, anhydrous ethanol, and KH 550 is 20g:500mL:300mL:3mL; the rotation speed of the ball mill is 450r / min; the ball milling time is 40min;
[0049] S32, take the material C and deionized water, mix them, stir at 80°C for 40min, add aniline and 5-sulfosalicylic acid, continue stirring for 7h, cool to room temperature, add ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, stir for 5h, add sodium hydroxide solution, stir for 4h, let stand for 16h, filter, wash the solid phase, and vacuum dry at 40°C for 24h to obtain the wear-resistant filler; the dosage ratio of the material C, deionized water, aniline, 5-sulfosalicylic acid, ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, and sodium hydroxide solution is 2g:200mL:11g:16g:26g:0.3g:0.08g:30mL; the concentration of the sodium hydroxide solution is 0.1mol / L.
[0050] Comparative Example 1
[0051] The difference from Example 2 is that material A is not added during the preparation of the laser anti-counterfeiting coating.
[0052] Comparative Example 2
[0053] The difference from Example 2 is that no wear-resistant filler is added during the preparation of the laser anti-counterfeiting coating.
[0054] Comparative Example 3
[0055] The difference from Example 2 is that the preparation of the wear-resistant filler comprises the following steps:
[0056] Sodium montmorillonite and deionized water are mixed, stirred at 80°C for 35 minutes, aniline and 5-sulfosalicylic acid are added, stirring is continued for 6.5 hours, cooled to room temperature, ammonium persulfate, aluminum nitrate nonahydrate and nickel nitrate hexahydrate are added, stirring is continued for 4.5 hours, sodium hydroxide solution is added, stirring is continued for 3.5 hours, standing for 14 hours, filtering, washing the solid phase, and vacuum drying at 40°C for 24 hours to obtain the wear-resistant filler; the dosage ratio of the sodium montmorillonite, deionized water, aniline, 5-sulfosalicylic acid, ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate and sodium hydroxide solution is 1.5g:200mL:10.5g:15.5g:25.5g:0.25g:0.07g:25mL; the concentration of the sodium hydroxide solution is 0.1mol / L.
[0057] Comparative Example 4
[0058] The difference from Example 2 is that the preparation of the wear-resistant filler comprises the following steps:
[0059] S31, taking sodium montmorillonite and deionized water, mixing, stirring at 75°C for 1.5h, adding anhydrous ethanol and KH 550, continuing stirring for 3.5h, transferring to a ball mill for ball milling, taking out, washing, and vacuum drying at 80°C for 7.5h to obtain material C; the amount ratio of the sodium montmorillonite, deionized water, anhydrous ethanol, and KH 550 is 18g:500mL:250mL:2.5mL; the rotation speed of the ball mill is 425r / min; the ball milling time is 35min;
[0060] S32, take the material C and deionized water, mix them, stir at 80°C for 35 minutes, add aniline and 5-sulfosalicylic acid, continue stirring for 6.5 hours, cool to room temperature, add ammonium persulfate and aluminum nitrate nonahydrate, stir for 4.5 hours, add sodium hydroxide solution, stir for 3.5 hours, let stand for 14 hours, filter, wash the solid phase, and vacuum dry at 40°C for 24 hours to obtain the wear-resistant filler; the dosage ratio of the material C, deionized water, aniline, 5-sulfosalicylic acid, ammonium persulfate, aluminum nitrate nonahydrate, and sodium hydroxide solution is 1.5g:200mL:10.5g:15.5g:25.5g:0.32g:25mL; the concentration of the sodium hydroxide solution is 0.1mol / L.
[0061] Comparative Example 5
[0062] The difference from Example 2 is that the preparation of the wear-resistant filler comprises the following steps:
[0063] S31, taking sodium montmorillonite and deionized water, mixing, stirring at 75°C for 1.5h, adding anhydrous ethanol and KH 550, continuing stirring for 3.5h, transferring to a ball mill for ball milling, taking out, washing, and vacuum drying at 80°C for 7.5h to obtain material C; the amount ratio of the sodium montmorillonite, deionized water, anhydrous ethanol, and KH 550 is 18g:500mL:250mL:2.5mL; the rotation speed of the ball mill is 425r / min; the ball milling time is 35min;
[0064] S32, take the material C and deionized water, mix them, stir at 80°C for 35min, add aniline and 5-sulfosalicylic acid, continue stirring for 6.5h, cool to room temperature, add ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, stir for 4.5h, add sodium hydroxide solution, stir for 3.5h, let stand for 14h, filter, wash the solid phase, and vacuum dry at 40°C for 24h to obtain the wear-resistant filler; the dosage ratio of the material C, deionized water, aniline, 5-sulfosalicylic acid, ammonium persulfate, nickel nitrate hexahydrate, and sodium hydroxide solution is 1.5g:200mL:10.5g:15.5g:25.5g:0.32g:25mL; the concentration of the sodium hydroxide solution is 0.1mol / L.
[0065] Performance Testing
[0066] The laser anti-counterfeiting coatings prepared in Examples 1-3 and Comparative Examples 1-5 were respectively uniformly coated on the tinplate sheets polished with sandpaper using a 60 μm wire rod at room temperature, and baked at 50° C. for 120 min to obtain a coating with a thickness of 30±1 μm. The obtained coatings were subjected to performance tests according to the following standards / methods, and the test results are shown in Table 1 below:
[0067] Conduct pencil hardness test according to standard GB / T6739-2006;
[0068] Use steel wool (0000#) wiping method and load 500g weight to carry out scratch resistance test;
[0069] Wear resistance test is carried out according to standard GB / T 1768-2006;
[0070] The coatings prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-5 were subjected to surface roughness testing. A 2205 type surface roughness meter was used to measure the average surface roughness (Ra) of the coatings prepared in Examples 1-3 and Comparative Examples 1-5, respectively. The test results are shown in Table 1 below.
[0071] Table 1
[0072] Pencil hardness Scratch resistance: 500g / time Wear resistance / g Surface roughness (Ra) Example 1 5H 133 0.0018 0.234 Example 2 5H 136 0.0015 0.238 Example 3 5H 134 0.0017 0.235 Comparative Example 1 3H 108 0.0083 0.217 Comparative Example 2 2H 52 0.0147 0.211 Comparative Example 3 3H 78 0.0041 0.223 Comparative Example 4 4H 104 0.0025 0.227 Comparative Example 5 4H 106 0.0024 0.228
[0073] As can be seen from Table 1, the laser anti-counterfeiting coatings prepared in Examples 1-3 of the present application have excellent wear resistance and scratch resistance. The present application optimizes the formula composition, introduces epoxy esters containing benzene ring structures and carbon-carbon double bonds and copolymerizes with various acrylates to obtain a denser network structure, increase the surface micro-roughness of the coating, and improve the wear resistance and scratch resistance of the coating. At the same time, wear-resistant fillers are added, and through the synergistic effect of aluminum and nickel, polyaniline nano-metal rods are generated to increase cross-linking sites, so that the coating has a higher hardness, further improving the wear resistance and scratch resistance of the coating.
[0074] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a laser anti-counterfeiting coating, characterized in that: The preparation method of the laser anti-counterfeiting coating comprises the following steps: S1, take α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl) propane, and ethylene glycol butyl ether, mix them, stir and heat them to 100-110°C, add N,N-dimethylethylamine, stir for 4-6h, and obtain material A; S2, take acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, and material A, mix them, reflux and stir at 120-130° C. for 0.5-1h, cool to 75-85° C., add N,N-dimethylethylamine, stir for 20-30min, and obtain material B; S3, taking the material B, defoaming agent, wetting agent, adhesion promoter, wear-resistant filler, and deionized water, mixing, and stirring for 20-30 minutes to obtain the laser anti-counterfeiting coating; The preparation of the wear-resistant filler comprises the following steps: S31, mix sodium montmorillonite and deionized water, stir at 70-80°C for 1-2h, add anhydrous ethanol and KH 550, continue stirring for 3-4h, transfer to a ball mill for ball milling, take out, wash, and vacuum dry at 80°C for 7-8h to obtain material C; S32, take the material C and deionized water, mix them, stir at 80°C for 30-40min, add aniline and 5-sulfosalicylic acid, continue stirring for 6-7h, cool to room temperature, add ammonium persulfate, aluminum nitrate nonahydrate, and nickel nitrate hexahydrate, stir for 4-5h, add sodium hydroxide solution, stir for 3-4h, let stand for 12-16h, filter, wash the solid phase, and vacuum dry at 40°C for 24h to obtain the wear-resistant filler; In step S31, the dosage ratio of the sodium montmorillonite, deionized water, anhydrous ethanol, and KH 550 is 15-20 g: 500 mL: 200-300 mL: 2-3 mL; In step S32, the dosage ratio of material C, deionized water, aniline, 5-sulfosalicylic acid, ammonium persulfate, aluminum nitrate nonahydrate, nickel nitrate hexahydrate, and sodium hydroxide solution is 1-2 g: 200 mL: 10-11 g: 15-16 g: 25-26 g: 0.2-0.3 g: 0.06-0.08 g: 20-30 mL; In step S31, the rotation speed of the ball mill is 400-450 r / min; and the time of the ball mill is 30-40 min.
2. The method for preparing a laser anti-counterfeiting coating according to claim 1, characterized in that: In step S1, the mass ratio of α-eleostearic acid, 2,2-bis-(4-glycolylaminophenyl)propane, ethylene glycol butyl ether, and N,N-dimethylethylamine is 3-4:6-8:10-15:0.01-0.
012.
3. The method for preparing a laser anti-counterfeiting coating according to claim 1, characterized in that: In step S2, the mass ratio of acrylic acid, n-butyl methacrylate, methyl methacrylate, hydroxypropyl acrylate, tert-butyl perbenzoate, 2,4-diphenyl-4-methyl-1-pentene, material A, and N,N-dimethylethylamine is 8-10:20-22:36-38:8-10:0.4-0.6:2-3:10-12:1-2.
4. The method for preparing a laser anti-counterfeiting coating according to claim 1, characterized in that: In step S3, the mass ratio of material B, defoaming agent, wetting agent, adhesion promoter, wear-resistant filler and deionized water is 60-70: 0.6-0.8: 0.6-0.8: 0.6-0.8: 2-3: 12-16.
5. A laser anti-counterfeiting coating prepared by the preparation method according to any one of claims 1 to 4.
6. A laser transfer film, characterized in that: Including the laser anti-counterfeiting coating described in claim 5.
Citation Information
Patent Citations
Waterborne epoxy ester resin composition and preparation method thereof and water-based paint prepared from same
CN101851396A
Aqueous-transfer direct-plated laser coating material for cigarette packets and preparation method
CN107266986A